A bygge en samling - Boym, Per Bjarne (Oslo : National Museum of Contemporary Art, 2001)
Anselmo, Giovanni ; Baird, Vanessa ; Bak Jensen, Per ; Balka, Miroslaw ; Bergman, Anna-Eva ; Bjarre, Bjorn ; Bjorlo, Per Inge ; Boltanski, Christian ; Book, Ingrid ; Brand, Paul ; Darboven, Hanne ; Förg, Günter ; Gursky, Andreas ; Hedén, Carina ; Kristo, Arild ; Kurdol, Egil Martin ; Lawler, Louise ; Melgaard, Bjarne ; Moffatt, Tracey ; Nyborg, Hege ; Pahr-Iversen, Kjell ; Robinson, Robert A. ; Rumohr, Knut ; Rydhagen, Jenny Maria ; Slaattelid, Mari Johanne ; Smithson, Robert ; Vigeland, Tone
Noors & Engels
To Build a Collection : Acquisitions 1997-2000, National Museum of Contemporary Art, Oslo, 20.01 - 11.03.2001
boek
Keywords: Oslo